An innovative approach to the treatment of Gaucher disease and possibly other metabolic disorders of the brain - Brady, Roscoe O. (J Inherit Metab Dis, 2012)
The extraordinary benefit of enzyme replacement therapy (ERT) on the systemic manifestations of Gaucher disease was demonstrated in 1991. Since that time, investigators have devoted substantial effort to improve the delivery of enzymes to the brain because many hereditary metabolic disorders are characterized by extensive central nervous system involvement. Because the required supplemental enzyme is too large to cross the blood-brain barrier (BBB), ERT for central nervous system involvement was out of the question at that time. Several innovative strategies that have been reported to overcome this impediment are discussed. Recent investigations have provided additional insight concerning the pathogenesis of enzyme deficiency disorders. For many years it was presumed that alterations of the amino acid sequence of enzymes such as glucocerebrosidase reduced the catalytic activity of the enzyme. It has recently been shown that the decrease of glucocerebrosidase activity was the result of a quantitative loss of the amount of this enzyme. Significant increases of its activity were obtained with small molecule inhibitors of histone deacetylase that cross the BBB. The effect of such materials on neuronopathic Gaucher disease and other CNS metabolic disorders is discussed.